Capturing the invisible. Sociotechnical imaginaries of energy. The critical overview. (16th November 2021) - Rudek, Tadeusz Józef
Abstract: While the need and general direction of the energy transition are widely accepted, the implementation has different dynamics throughout the world. Sociotechnical imaginaries concept, bridging the science, policy, and society, seems promising in understanding and explaining the global differences. The present paper analyses 135 abstracts that contain the topic keywords, sociotechnical imaginaries, published in international, peer-reviewed scientific journals during the last 11 years. Further on, the author conducted a qualitative and quantitative analysis of 43 energy-related articles to offer a panoramic overview of sociotechnical imaginaries in energy research out of the more extensive background. The paper aims to present a critical overview of the concept usage in energy studies to identify incoherences and blind spots in concept usage. What is more, this research intents to show the promising direction of using sociotechnical imaginaries. It also proposes new operationalisation and theoretical frame as well as potentially contributes to policymaking.